Kyrgyz Republic - Profile and Dynamics of Poverty and Inequality, 2009 - World Bank (World Bank, 2012)
Poverty reduction is an important goal for governments of many developing countries. This goal is synonymous with economic development and achieving a higher quality of life for all population groups. Thus, monitoring the dynamics of poverty and inequality is implicit in the monitoring of progress in societal development. As the vast literature shows, development progress to a large extent depends on economic and social policies and economic growth. Thus, identifying the relationship between relevant economic variables and poverty and inequality indicators may provide policy guidance on what has furthered the country's progress. The report consists of two main parts. The first part discusses poverty and inequality for 2009 and, thus, from a static perceptive. So, the first section describes and discusses the main features and correlates of the poor. The goal is to provide a brief overview of poverty in the Kyrgyz Republic and describe the characteristics of households and the poor. This is achieved by considering the poverty incidence among households and individuals differentiated by such characteristics as age, household size, employment status, educational attainment, geographic location, gender of the household head, and internal migration status of the household head. This section also incorporates some insights on poverty from a recent study carried out in the Kyrgyz Republic related to the poverty and social impact analysis of selected reforms in the social protection sector. The second section discusses the dynamics of poverty and inequality in the Kyrgyz Republic during 2006-2009. This section relates the trends of macro indicators gross domestic product, or GDP, growth in different sectors of the economy, the consumer price index [CPI], remittances, and social budget expenditures) to changes in micro indicators of interest (poverty and inequality). The objective is to integrate into one coherent picture the recent macro and micro developments. The period of 2006-2009 coincided with the food price volatility and financial crisis of 2008-09. So the distinct feature of this report is that the impact of international instabilities is reflected in the assessment of poverty and inequality. The report uses two types of data: the macroeconomic, national accounts data as regularly reported by the National Statistical Committee of the Kyrgyz Republic (NSC), Ministry of Finance, and National Bank of the Kyrgyz Republic, and microeconomic, primary data derived from the Kyrgyz Integrated Household Survey, or KIHS (also collected by the NSC). These two might not always be consistent with each other, but they do complement one another to provide useful policy insights.